TINJAUAN HUKUM ISLAM TERHADAP FATWA MUI NO 02 TAHUN 2021 TENTANG KEHALALAN VAKSIN COVID-19 SINOVAC - Safrida S; Fauzah Nur Aksa; T Saifullah (Fakultas Hukum Universitas Malikussaleh, 2022)
The determination of various types of Covid-19 vaccine products that have been determined by the Indonesian government as well as promises to provide Covid-19 vaccine products cannot be guaranteed to be halal, thayib and safe to use, especially for Indonesian people who are Muslim. On this basis, there was a debate in Indonesia regarding the halalness of thecovid 19 vaccine. Therefore, in order to organize and be able to successfully distribute the vaccine, as well as the consumption of the vaccines that have been purchased. So the Indonesian government cooperates with the Indonesian Ulema Council (MUI) by referring to the Fatwa of the Indonesian Ulema Council (MUI) NO. 02 of 2021 which issues a fatwa regarding the law that the Covid-19 vaccine produced by Sinovac Life Sciences Co. Ltd. China and PT. Bio Farma (Persero) is legal, holy and halal. This study aims to find out in detail the legal basis for the MUI to issue a fatwa that the Sinovac vaccine is halal and to know and be able to analyze the views of Islamic law on the MUI Fatwa No. 02 of 2021 regarding the halalness of the Sinovac vaccine. This research is legal-normative research, namely research that uses law to justify a legal event. This type of research is descriptive-analytic research using library research. Based on the results of the study, it is known that there are 7 basics used by the MUI in determining the halalness of the Sinovac vaccine, namely: First, the opinion of the Ulama; Second, MUI Fatwa No. 04/2016 on Immunization; Third, MUI Fatwa Number 01 of 2010 concerning the Use of Microbes and Microbial Products in Food Products; Fourth, MUI Fatwa Number 45 of 2018 concerning the Use of Blood Plasma for Medicinal Ingredients; Fifth, the report and explanation of the audit results of the LPPOM MUI Auditor Team together with the MUI Fatwa Commission to Sinovac and PT Bio Farma; Sixth, the opinion of the participants of the Fatwa Commission meeting on January 8, 2021; Seventh, BPOM's decision to give approval for emergency use and guarantee of safety, quality, and efficacy for the Sinovac vaccine, which is one indicator that the vaccine meets thayyib qualifications. In addition, it can be believed that the Covid-19 vaccine produced by Sinovac is holy and halal. Those are the notes on the results of the MUI Fatwa regarding the halal certification of vaccines that were described in the Plenary Session of the MUI Fatwa Commission on January 8, 2020 and the MUI Fatwa No. 2 of 2021 has been issued/decided.